Aerobic Rice for Nutrient and Water Use Efficiency in Lateritic Soils of Kerala - P, Geetha; Sureshkumar, P. (International Journal of Bio-resource and Stress Management, 2018)
Field experiments on aerobic and flooded systems of rice were conducted in lateritic soil to study the nutrient and water use efficiency in these systems.Three doses of lime (as per package of practices recommendations, KAU, as per ∆pH and as per SMP buffer method) were imposed in plots of 20 m2 area in RBD with four replications. In situ measurement of pH and redox potential was done under both systems. The increase in pH and EC in both systems was in maintaining a linear relationship to the quantity of lime applied. The organic carbon content and N in plant were higher under aerobic environment. Available P and boron were highest under flooded system. Available Fe and hence its concentration in plant could be reduced by keeping the rhizosphere aerobic; enhanced the availability and uptake of P, K and Zn. Fresh root CEC as well as apparent free space were also found higher under aerobic system. Aerenchymatic tissue in the roots was observed only under flooded system. Root mass, shoot mass and root length at active tillering stage indicated that aerobic environment enhanced root and shoot growth when compared to flooded system. Number of tillers hill-1, number of panicles hill-1 and number of grains panicle-1 were higher under aerobic system. Grain yield and straw yield were also higher under aerobic system. The water requirement was reduced by 57% in aerobic rice.